Sinergi Segitiga Emas: Gerakan Orang Tua Mengajar sebagai Strategi Membangun Ekosistem Belajar Motivasional di SD Karangmloko 1 - Utami, Linda Tri; Gularso, Dhiniaty (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
This qualitative study aims to analyze the implementation of the Parent Teaching Movement program at SD Negeri Karangmloko 1 in building a synergistic education trilogy between the school, parents, and students. The focus of the study is to describe how this program increases students' learning motivation through direct parental involvement in the learning process. Data was collected through participatory observation, in-depth interviews with the principal, teachers, parents, and students, as well as document studies, with triangulation techniques to ensure data validity. The results of the study indicate that the Parent Teaching program, implemented through various activities such as career days and skills workshops, successfully creates a motivational learning ecosystem. Parental participation as resource persons not only provides contextual learning experiences for students but also strengthens communication between the school and families. Collaborative support from the school committee and teachers is a key factor in creating an inclusive learning environment and positively impacts the increase in students' learning motivation as well as the strengthening of their character. The findings of this study highlight that the trilogy education collaboration model through the Parents Teaching Movement program is effective in creating meaningful and relevant learning experiences for students' real lives, while also strengthening the synergistic relationship among the three pillars of education.